Utilization of Computer-Based Learning Technology to Enhance Students’ Arabic Language Profeciency: A Study at MIMA Zainul Hasan Balung - Al Maidah, Sandia; Ilma, Maulia Humaini; Cahyani, Budiati (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
This study aims to analyze the implementation of Computer-Based Learning (CBL) methods in Arabic subjects at MIMA Zainul Hasan Fullday School Balung Jember. This study tries to identify the ad-vantages, challenges, and impacts on students’ language skills. Using descriptive qualitative methods, data were collected trough observation, interviews, and documentation. The results of the study indicate that CBL, especially trough simulations, educational games, and interactive multimedia, is effective in increasing students’ motivation, engagement, and Arabic language proficiency. CBL enables personalized, flexible, and engaging learning with instant feedback. However, challenges such as limited infrastructure and teachers’ technological competence still exist. This study concludes that CBL is a relevant method fo 21st-century education, but requires curriculum development, teacher training and continuous technological support to optimize its implementation in madrasah.